BLUEPRINT ELEKTRONIK MODUL ENERGI OLAHRAGA MATAKULIAH ILMU GIZI OLAHRAGA DALAM HYBRID LEARNING - Mashuri, Hendra; Gunarto, Peby; Adi, I Putu Panca (Fakultas Ilmu Keolahragaan Unimed, 2024)
Developing electronic teaching materials for sports energy in hybrid learning is necessary for lecturers teaching sports nutrition courses. Electronic teaching materials are able to help students learn independently and in groups without time and place limits. Electronic teaching materials are developed by considering student requirements, student characters, study program curriculum, and teaching systematics. Designing electronic teaching materials by making electronic teaching material storyboards, organizing teaching materials, making attractive covers and templates, and converting teaching materials to flipbooks